Development and Validation of RP-HPLC Method for the Determination of Dexrabeprazole Sodium - Semra Yılmazer Keskin; Cihansel Unlu; Ebru Nurdan Şentürk (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2021)
A rapid and simple liquid chromatographic method was developed for the quantitative determination of dexrabeprazole sodium in the tablet dosage form. The reverse-phase chromatographic analysis was carried out by using a C-18 column. The acetonitrile-phosphate buffer mixture was used as the mobile phase. The obtained retention time was 4.33∓0.02 min. by using 50:50 (v:v) acetonitrile:phosphate buffer(pH 7) and 1.0 mL/min. flow rate. Quantification of the analyte was based on measuring the peaks areas at 272 nm. The analytical performance of the developed RP-HPLC method was validated with respect to accuracy, precision, linearity, stability, and robustness. The obtained linearity range was 77-143 mg/L and the correlation coefficient was 0.9989. The obtained LOD and LOQ values were 0.010 mg/L and 0.034 mg/L, respectively.